ANALISIS KEDALAMAN KEUANGAN, REDISTRIBUSI FISKAL DAN PENDIDIKAN PADA KETIMPANGAN PENDAPATAN DI INDONESIA TAHUN 2010–2018 - Tiofan Bagus Wicaksono Situngkir; Syafri Syafri (Media Ekonomi, 2020)
This Study aims to analyze the effect credit per GDP, General allocation funds (DAU), And average length of scholling in the gini ratio. The data used is secondary data, derived from the publication of the central bureau of statistics, directorate general of fiscal balance and bank indonesia, in the form of annual data from 2010 to 2018. the analytical method used is panel data regression with the number of objects in 32 provinces in indonesia, except dki jakarta and north kalimantan provinces. The results showed that credit per grdp had a significant positive effect on the gini ratio at the 95% confidence level, the general allocation funds (dau) had a significant positive effect on the gini ratio at the 99% confidence level and the average length of schooling had a significant negative effect on the gini ratio at the level of confidence. 99% confidence.